Powers of the South African National Defence Force to enforce South African law at sea - Smit, Andre (Scientia Militaria - South African Journal of Military Studies, 2017)
Law enforcement at sea requires specialised capabilities, training and legislation due to the unique legal and physical environment within which it is conducted. The South African National Defence Force (SANDF) is increasingly deployed for enforcing South African law at sea, and a constitutional democracy with entrenched human rights requires that the SANDF performs this function in a lawful and compliant manner with reference to international and domestic law. The present study sought to contribute to a greater understanding of the legal framework for law enforcement at sea by the military, and surveyed the applicable international and domestic legal prescripts to describe briefly the nature of law enforcement tasks involved. The law enforcement powers of the SANDF are pointed out in this article and discussed in the context of the applicable legal prescripts that straddle the boundaries between a collection of different areas of law. Some observations are made on possible human rights concerns, cooperation with other government departments, and considerations for the military commander are pointed out before conclusions are drawn.